Penerapan Video Animasi Interaktif untuk Mengenalkan Nilai-nilai Keagamaan pada Anak (THUFULA, 2021)
The ability to recognize religious values is important for children aged 4-5 years, because it will greatly affect the development of children at the next level. The ability to recognize religious values will develop well if it is supported by the right media. This study aims to promote interactive animation video learning media to help the ability to recognize religious values of children aged 4-5 years. Interactive animated video is a combination of visual-based media with audio media. This type of research was Research and Development (R&D) from Plomp. The research sample was 30 children aged 4-5 years in Permata Hati Jajar Islamic Kindergarten, Surakarta. Data collection techniques used questionnaires and children’s performance. Data analysis used descriptive quantitative and qualitative descriptive methods. The results of the data analysis showed that 90% of material experts were obtained, media experts were 81%, teachers were 88%, development trials were 89%, implementation was 94%. The overall assessment results was obtained an average score of 88%. The average score that had been obtaining showed that the interactive animated video developed was very suitable to be use as a medium to help introduce religious values in children aged 4-5 years. Based on these results, it can be concluded that the interactive animated videos developed were able to increase the ability to recognize religious values in children aged 4-5 years.